The Routledge introduction to the American ghost story - Brewster, Scott; Weinstock, Jeffrey Andrew 1970- (Routledge, Taylor & Francis Group, 2025)
"This book traces the historical development of the American ghost story from its Indigenous, Puritan and Enlightenment origins to its heyday in the nineteenth century and continued vibrancy in modern literary and visual culture. It explores the main tropes, thematic preoccupations, principal settings and stylistic innovations of literary ghost stories in the United States, and the ghost story's rich afterlife in cinema, television and digital culture. Throughout, the role played by ghost stories in nation-building, and the questions these tales raise about race, class, sexuality, religion and science, will be examined. The book examines major practitioners in the field, such as Nathaniel Hawthorne, Washington Irving, Shirley Jackson, Henry James, Stephen King, Toni Morrison, Joyce Carol Oates and Edith Wharton, alongside prominent ghost narratives in cinematic, televisual and online form, including podcasts, gaming and ghost-hunting apps. This study also gives a new prominence to neglected or less familiar authors, including BIPOC writers, who have helped to shape the American ghost story tradition."
Keywords: Gespenstergeschichte; Gespenst; Film; USA; Ghost stories, American / History and criticism